Revolutionizing healthcare through artificial intelligence and Internet of Things applications - Kaushik, Keshav; Dahiya, Susheela; Dwivedi, Ashutosh Dhar 1988-; Aggarwal, Shilpi 1983- (Advances in healthcare information systems and administration, 2023)
The objective of the book is to give a greater knowledge of how AI affects healthcare and medical efficacy in order to improve output